AN RISING MENACE TO SOCIETY: A CASE SERIES ON IDIOPATHIC INTRACRANIAL HYPERTENSION - RATHWA, SANJAYKUMAR; RATHWA, PRATIKSHA; NIRGUDE, VRUSHABH; Nirgude, VRUSHABH (International Journal of Current Pharmaceutical Research, 2025)
Idiopathic intracranial hypertension (IIH) is a complex neurological disorder characterized by elevated intracranial pressure. This case series examines the clinical manifestations and therapeutic management of IIH. The patients presented with headache, visual disturbances, and diplopia, with the latter symptom attributed to abducens nerve palsy. Our findings highlight the importance of prompt recognition and treatment of IIH, as delayed diagnosis can lead to irreversible visual loss and other complications. This case series provides valuable insights into the presentation and management of IIH, emphasizing the need for increased awareness and vigilance among healthcare providers.